Synthesis and photophysicochemical studies of poly(ethylene glycol) conjugated symmetrical and asymmetrical zinc phthalocyanines - Dincer, Hatice; Mert, Humeyra; Caliskan, Emel; Atmaca, Goknur Yasa; Erdogmus, Ali (ELSEVIER, 2015)
Synthesis and characterization of poly(ethylene glycol) conjugated symmetrical and asymmetrical zinc phthalocyanines (ZnPcs) is described. Copper (I) catalyzed azide-alkyne cycloaddition (CuAAC) click reaction between azide functional methoxypoly(ethylene glycol) (mPEG-N-3) and tetra terminal alkynyl substituted ZnPc yields star polymer with ZnPc core. Furthermore, CuAAC click reaction between asymmetrically terminal alkynyl substituted zinc phthalocyanine (aZnPc) and mPEG-N-3 yields aZnPc end functionalized PEG. Spectral, photophysical (fluorescence quantum yield), photochemical (singlet oxygen (Phi(Delta)), and photodegradation quantum yield (Phi(d)) properties of the symmetrically, and asymmetrically PEGylated ZnPcs are investigated to be used as sensitizers in photodynamic therapy (PDT). The quantum yield values of fluorescence (Phi(F)) and singlet oxygen generation (Phi(Delta)) for water soluble symmetrically PEGylated ZnPc in aqueous solution are calculated as 0.01 and 0.14 respectively, suggesting its potential as photosensitizer in PDT treatment. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Symmetrical zinc phthalocyanine; Asymmetrical zinc phthalocyanine; Click; Star polymer; Photodynamic therapy; HALOGENATED SILICON(IV) PHTHALOCYANINES; WATER-SOLUBLE PHTHALOCYANINES; STAR POLYMERS; PHOTOSENSITIZER; PORPHYRINS; PEGYLATION; CHLORO; CHAINS; Chemistry